Pengenalan dan Pembuatan Eco-enzyme di Lingkungan Universitas Muhammadiyah Sorong Sebagai Alternatif Pengurangan Sampah Organik - Abu, Nur; Dwangga, Mierta; Ibal, La; Yasin, Azalia Fajri; Rahmatullah, Azwar; Marasabessy, Umar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Organic waste is the most common in the Muhammadiyah University of Sorong's (UNAMIN) environment. The presence of organic waste can cause unpleasant odors, reduce the aesthetic value of the campus environment, and cause disease. Eco enzyme is a waste fermentation process in the form of fruit peels and vegetable remains. Eco-enzymes are widely used in household, agricultural, and fishing activities. One alternative to reducing organic waste in the UNAMIN campus environment is introducing and making Eco-enzymes from fruit waste. This community service activity aims to increase the knowledge and skills of the UNAMIN campus community, especially in the environmental engineering study program regarding making Eco enzymes from orange peel. This activity is specifically for environmental engineering students, hoping that ecological engineering study program students will provide an example for other study programs within the Mumahhadiyah University of Sorong. Until now, we have not handled wet organic waste in the campus environment. Eco enzyme can be an alternative use of wet (organic) waste that is environmentally friendly and easy for the campus community to use. The results of this Eco enzyme can be used as liquid fertilizer for gardens on the UNAMIN campus. The organic waste processed into enzymes is obtained from the campus canteen. Apart from being used as liquid fertilizer, this Eco enzyme is also used to clean fish ponds at the fisheries faculty.